AKSELERASI PENGEMBANGAN AGRIBISNIS, KELEMBAGAAN KEMITRAAN IMPLEMENTASI MEWUJUDKAN PENSEJAHTERAAN PETANI HORTIKULTURA - Roosganda Elizabeth; Giovanni Inez EM; Geraldy Samuel Ivan (Universitas Galuh Ciamis, 2021)
For farmers, the partnership relationship has great benefits, which are relatively stable with market certainty. While the benefits for partners are the certainty of obtaining raw materials in accordance with the required specifications. Using a qualitative description method, this paper aims to examine and present the conditions and institutional performance of the processing industry partnership in the marketing of horticultural products. Market certainty is the hope and main goal of farmers in pursuing each of their farming activities, in addition to obtaining maximum yields of course. Various agro-industry business actors, directly or indirectly in the procurement of raw materials, mostly still come from traders/suppliers. In a cooperative partnership relationship, farmer groups / farmer group associations are more burdened with obligations while their rights are still limited. The benefits of studying marketing partnership institutions and their development perspectives related to efforts to accelerate and implement agribusiness development to improve the welfare of their farmers, of course, are needed, especially as a liaison between farmers and users of their farm products. The perspective of partnership development is still very open, among others due to: (a) both parties obtain mutually beneficial benefits; (b) demand for processed products is increasing along with population growth. Institutional partnerships act as partners to market farm production in a wider and varied range. The partners are indicated to continue to provide the opportunity to sell to the free market if the price is better.